Application of Imidazole‐2‐thione Substituents in Low‐Coordinate Phosphorus Chemistry – Probing the Scope. Issue 22 (12th July 2016) - Majhi, Paresh Kumar; Koner, Abhishek; Schnakenburg, Gregor; Kelemen, Zsolt; Nyulászi, László; Streubel, Rainer
Abstract : A variety of (2‐thioxoimidazol‐4‐yl)phosphanes have been synthesized with the prospect of further functionalization. Following a standard reaction protocol, P ‐amino (2a, b ), P ‐chloro (3a, b ), and P ‐hydrogeno (8a ) phosphane derivatives were synthesized. Treatment of chlorophosphanes3a, b with Lewis acids in dichloromethane/diethyl ether did not afford the expected phosphenium cation, instead ethoxyphosphane derivatives5a, b were isolated. Treatment of secondary phosphane8a with potassium hexamethyldisilazide afforded 2‐thioxoimidazol‐4‐yl‐substituted phosphanide derivative10a, which was used to access dinuclear phosphanido borane11a and tungsten complexes12a . Furthermore, the first strong NMR evidence for P ‐anionic bis(imidazole‐2‐ylidene)13a is provided. The first attempts to synthesize an (2‐thioxoimidazol‐4‐yl)‐substituted phosphanyl radical or its dimer, the tetrakis(2‐thioxoimidazol‐4‐yl)‐substituted diphosphane, led exclusively to tris(2‐thioxoimidazole‐4‐yl)phosphane14a . These compounds were fully characterized spectroscopically and the structures of2a, 3a, 7b, 8a, 10a, 11a, and14a were determined by single‐crystal X‐ray crystallography. The challenges associated with the synthesis of some of the titled compounds were studied computationally. Abstract : 2‐Thioxoimidazole substituents have been investigated for the first time in the synthesis of low‐coordinate phosphorus compounds of typesI –III and revealed some surprising new features. The synthesis of some of the compounds have been studied computationally to provide further insights into some of the difficulties encountered in the syntheses.